The Electron Spin and Magnetic Properties of Cluster Fe3Ni3 - ZHENG Xinxi; FANG Zhigang; WANG Qian; XU You; JING Runtian (Journal of Harbin University of Science and Technology)
In order to explore the electron spin and magnetic properties of amorphous alloy Fe-Ni binary system, and provide theoretical support for its macroscopic excellent magnetic properties, the cluster Fe3 Ni3 was designed as a local structure model. Based on density functional theory, full parameter optimization calculation is performed under B3LYP/Lanl2dz (level) , and finally five triplet optimized configurations are obtained. The single-electron distribution of each optimized configuration is analyzed from the angle of Mulliken spin population, and its magnetic properties are studied by the electron spin density, magnetic moment and orbital state density of each configuration. The results show that in all optimized configurations of Fe3 Ni3 clusters, the single electrons of each atom are mainly distributed in the d orbital, and the single electrons of Fe atoms are more than those of Ni atoms and the spin directions are opposite. At the same time, the contribution of Fe atoms to the cluster magnetism is also larger than the Ni atom; the d orbital of the cluster Fe3 Ni3 plays a major role in the magnetic properties of the cluster; the ɑ and β electrons on the specific energy segments of some of the s and p orbitals can be spin-coupled and converted.